Controlling factors on the formation and distribution of “sweet-spot areas” of marine gas shales in South China and a preliminary discussion on unconventional petroleum sedimentology - Qiu, Zhen; Zou, Caineng (Journal of Asian earth sciences, 2020)
[Display omitted] •The formation of sweet-spot intervals is mainly controlled by four geological factors.•Sweet-spot areas were “born” in regional anoxic shelf with stable tectonics.•Sweet-spot areas could be “preserved” in relatively stable tectonic zones.•Sweet-spot areas would be the result of coupling sedimentology from geological events. Shale gas resources in China are abundant with the marine shales accounting for the largest proportion, i.e. 13 × 1012 m3. The Wufeng-Longmaxi Shale system deposited across the Late Ordovician and Early Silurian transition in South China is currently the target for shale gas exploration and development in China. Its annual output in 2018 reached 10.8 × 109 m3, making China the largest shale gas production region outside North America. Within this shale system the sweet-spot intervals of shale gas formed vertically and sweet-spot areas of shale gas formed regionally. The sweet-spot intervals occur mainly at the bottom of the Wufeng-Longmaxi Shale and are 10–40 m in thickness. The sweet-spot interval is characterized by high total organic carbon (TOC) and gas contents, relatively high porosity, high brittle mineral content, and abundant lamination fissures and fractures. The formation of shale gas sweet-spot intervals is mainly controlled by four factors in South China. They are anoxic shelf environment, abundant nano-pores in organic matter, sealed roof and floor strata, and abundant lamination and high silica content in shale, respectively. As the regional extension of the sweet-spot intervals, the formation of the sweet-spot area requires all the controlling factors for the sweet-spot interval. It was “born” in regional anoxic shelf with stable tectonics and “preserved” in relatively stable tectonic zones. Three sweet-spot areas are identified for the Wufeng-Longmaxi Shale in South China, i.e. Fuling, Weiyuan-Fushun-Yongchuan and Changning-Zhaotong areas. The total area is about 2 × 104 km2 with technically recoverable resources of 3.3 × 1012 m3. In addition, with the rapid progresses of exploration and development of unconventional petroleum resources such as shale gas, the petroleum industry around the world extends to unconventional petroleum resources, gradually accomplishing an important change of petroleum geology research focus from conventional to unconventional. Unconventional petroleum geology research focuses on continuously or semi-continuously distributed sweet-spot areas, for which the formation would be the result of coupling sedimentology from several geological events such as global or regional tectonic activity, volcanic eruption, climate change, anoxic water, biotic mass extinction and radiation, and gravity current. It is necessary to innovatively construct new insights of unconventional petroleum sedimentology in order to enrich and improve the petroleum sedimentology research and its application. Therefore, the concept of unconventional petroleum sedimentology is proposed, and its research task, method, aim and importance are preliminarily discussed.